Nem herói, nem vilão: elementos da prática médica na atenção básica em saúde - Oliveira, D. O.; Cecilio, L. C. O.; Andreazza, R.; Cardoso, E. C.; Correia, T. (Ciência e Saúde Coletiva, 2018)
This paper discusses the elements of medical practice that contribute to understand its low adhesion to the guidelines set forth by the National Primary Health Care Policy. The material produced by two investigations led by the research team was put into use. In the former, through interviews involving managers and the social control in cities the State of São Paulo, Brazil, medical doctors (acknowledged as central professionals for the construction of the Brazilian National Health Care System – SUS), are referred to as important assets to explain the difficulties to form a qualified primary health care service: the so-called “villain doctors”. In the latter, through an ethnographic/cartographic research carried out in seven PHC Units in cities of São Paulo, the use of scenes showing the doctors in action and/or thinking over their jobs, and the health team observing their work, more complex medical doctors emerge: fragile professionals with a reduced set of instruments to act before the “social factor” that invades their practices, threatened in their autonomy, finding it hard to engage in teamwork, dispossessed of their regulatory functions, and unaware of the space reserved for primary practices: extremely human doctors – not heroes, not villains.